A stochastic criterion for the optimal investment process - Bondarenko, Julia; Bidyuk, Petro (Zielona Góra: Uniwersytet Zielonogórski)
The paper describes an approach to the construction of a criterion suitable for optimization of an investment project. An income growth resulting from realization of the investment project is considered as a time sequence of random variables. Then an expression is derived which characterizes the project cost at a sequence of time intervals it and raises a possibility to find the real income as a random variable.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka